Cultural History in Europe Institutions - Themes - Perspectives - Rogge, Jörg (Mainzer Historische Kulturwissenschaften, 2011)
What is the current state of discussion in Cultural History? Which European institutions engage exclusively in Cultural History and which topics do they address? And how will Cultural History develop in the future?These and other questions are raised by European scholars in the discussion of Institutions, Themes and Perspectives of Cultural History in this volume. It provides a profound overview of contemporary developments in Scandinavia, Finland, Great Britain, Latvia, Poland, Hungary, Austria, Switzerland, Germany, Italy and Spain